Linfadenectomia robótica retroperitoneal e pélvica de salvamento no câncer de próstata com recidiva linfonodal : técnica e série inicial - Fay, Carlos Eduardo Schio (2019)
Introduction: Despite primary treatment of prostate cancer with surgery or external radiation therapy, 20-40% of patients relapse within 5 years and 25-35% progress to metastatic disease. Salvage lymph node dissection has been proposed in patients with biochemical recurrence from prostate cancer and nodal involvement only, although the optimal template remains a question of debate. Herein we describe the technique of robotic extended salvage retroperitoneal and pelvic lymphadenectomy (sRPLND+PLND) for "node-only" recurrent prostate cancer and report the initial series. Materials and Methods: Twenty three patients underwent robotic sRPLND+PLND for "node-only" recurrent prostate cancer after definitive primary treatment as identified by PET/CT from September 2015 to December 2016 at Keck Hospital of University of Southern California (USC), Los Angeles, CA, USA. Our anatomic template extends from left renal vein and right renal artery cranially up to Cloquets node caudally, completely excising lymphatic-fatty tissue from aorto-caval and iliac vascular trees. Meticulous node-mapping assessed nodes at 4 prospectively-assigned anatomic zones. Results: Median age at salvage RPLND was 64 years (46-77 years), median BMI was 26.2 kg/m2 (21.7 – 33,8 kg/m2), previous primary treatment was radical prostatectomy in 20 patients (86%) and external radiation therapy in 3 patients (14%), median time from primary treatment was 42 months (1-163 months) and median PSA at sRPLND+PLND was 3.18 ng/mL (0.28 – 32.6 ng/mL). Median operative time was 305 minutes (209-433 minutes), blood loss was 100 ml (25-400 ml), and hospital stay was 1 day (1-6 days). No patient had intra-operative complication, open conversion or blood transfusion. Five patients had Clavien-Dindo Grade I post-operative complications: ileus in 2 patients (8,7%), thigh paresthesia in 1 patient (4,3%) and lymphorrhea in 2 patients (8,7%). Three patients had Clavien-Dindo Grade II complications: flank/scrotal ecchymosis in 1 patient (4,3%), chylous ascites in 1 patients (4,3%) and neuropraxia in 1 patient (4,3%); and 1 patient (4,3%) had lymphocele requiring drainage (IIIa). Final histology confirmed positive nodes in 19 patients (83%). Mean and median (range) number of nodes excised per patient was 84 and 89 (27-132 nodes) respectively. Mean and median (range) number of positive nodes was 24 and 6 (0-109 nodes) respectively. At 2 months post-operatively median (range) PSA was 0.41 ng/mL (0.01-8,3 ng/mL); median decrease of 79% (0-97,5%). In 4 patients the first PSA levels were less than 0,2ng/ml. Conclusion: Herein we describe the detailed technique of robotic high-extended salvage RPLND+PLND for "node-only" recurrent prostate cancer and present the initial experience. Robotic sRPLND+PLND duplicates open surgery, with superior nodal counts and decreased morbidity compared to the published literature. Longer follow-up is necessary to assess oncologic outcomes.